Surface acoustic wave devices for sensor applications - 刘博 陈晓 蔡华林 穆罕默德·阿里·穆罕默德 田祥光 陶璐琪 杨轶 任天令 (Journal of semiconductors, 2016)
Surface acoustic wave （SAW） devices have been widely used in different fields and will continue to be of great importance in the foreseeable future. These devices are compact, cost efficient, easy to fabricate, and have a high performance, among other advantages. SAW devices can work as filters, signal processing units, sensors and actuators. They can even work without batteries and operate under harsh environments. In this review, the operating principles of SAW sensors, including temperature sensors, pressure sensors, humidity sensors and biosensors, will be discussed. Several examples and related issues will be presented. Technological trends and future developments will also be discussed.